ANALISIS PUTUSAN HAKIM NOMOR 423/PDT.G/2023/MS.SGI TENTANG KEDUDUKAN HARTA WAKAF (MAWQUF) : Ditinjau Dari Fikih Muamalah Dan Qanun Aceh - Afni, Nur; Abdullah , Arifin; Eriyanti , Nahara (Program Studi Hukum Ekonomi Syariah Fakultas Syariah dan Hukum UIN Ar-Raniry, 2026)
This research examines disputes over mawquf assets arising from unilateral claims by heirs in Gampong Blanggalang, Pidie, highlighting the discrepancy between the principle of waqf permanence and private property claims. The study aims to analyze the legal considerations of Court Decision Number 423/Pdt.G/2023/MS.SGI and the protection mechanisms for waqf assets under Fiqh Muamalah and the Aceh Qanun. Adopting a normative juridical approach with a case study method, the data were sourced from the Sigli Syar’iyah Court decision and a literature review. The findings emphasize that the status of waqf is permanent and irrevocable. This study reveals the judicial recognition of the legality of customary waqf (wakaf adat) managed by the Baitul Mal as nazhir, despite the lack of formal administrative evidence. The judges prioritized the status of public assets over inheritance rights and categorized unilateral possession as an unlawful act. This ruling reflects the integration of positive law and local wisdom in strengthening the protection of religious assets. The research recommends the digitalization of waqf pledge administration to prevent similar disputes in the future.